Where a Vast Global Vaccination Program Went Wrong - Mueller , Benjamin; Robbins, Rebecca (Brazilian Journal of Implantology and Health Sciences, 2021)
After months of struggle, the U.N.-backed Covax alliance will soon have many more doses, promising relief for vaccine shortages in poorer countries. But it faces a deepening crisis: difficulties getting shots into arms as the Delta variant spreads. Deaths from Covid-19 were surging across Africa in June when 100,000 doses of the Pfizer-BioNTech vaccine arrived in Chad. The delivery seemed proof that the United Nations-backed program to immunize the world could get the most desirable vaccines to the least developed nations. Yet five weeks later, Chad’s health minister said, 94,000 doses remained unused. Nearby in Benin, only 267 shots were being given each day, a pace so slow that 110,000 of the program’s AstraZeneca doses expired. Across Africa, confidential documents from July indicated, the program was monitoring at least nine countries where it said doses intended for the poor were at risk of spoiling this summer. The vaccine pileup illustrates one of the most serious but largely unrecognized problems facing the immunization program as it tries to recover from months of missteps and disappointments: difficulty getting doses from airport tarmacs into people’s arms. Known as Covax, the program was supposed to be a global powerhouse, a multibillion-dollar alliance of international health bodies and nonprofits that would ensure through sheer buying power that poor countries received vaccines as quickly as the rich. Instead, Covax has struggled to acquire doses: It stands half a billion short of its goal. Poor countries are dangerously unprotected as the Delta variant runs rampant, just the scenario that Covax was created to prevent. The urgent need to vaccinate the world goes far beyond protecting people in poor nations. The longer the virus circulates, the more dangerous it can become, even for vaccinated people in wealthy countries. Without billions more shots, experts warn, new variants could keep emerging, endangering all nations. “Covax hasn’t failed, but it is failing,” said Dr. Ayoade Alakija, a co-chair of the African Union’s vaccine delivery program. “We really have no other options. For the sake of humanity, Covax must work.” More supplies are finally on the way, courtesy of the Biden administration, which is buying 500 million Pfizer doses and delivering them through Covax, the centerpiece of a larger pledge by wealthy democracies. The donated doses should begin shipping this month. But the Biden donation, worth 3.5 billion, comes with a caveat: To help fund it, the administration is diverting hundreds of millions of dollars promised for vaccination drives in poorer countries, according to notes from a meeting between Covax and American officials. Short on funding, those countries have had a hard time buying fuel to transport doses to clinics, training people to administer shots or persuading people to get them. Even as Covax officials scramble to fill that funding gap, the overriding question is whether the program can move beyond its mistakes, and beyond an imbalance of power that has left it at the mercy of wealthy countries and pharmaceutical companies. Pfizer, for example, balked at a direct deal with Covax this spring, interviews reveal, instead reaching an agreement through the Biden administration, an arrangement that hurt Covax’s credibility as an independent vaccine purchaser. This text is just a part of the original report by “Mueller, Benjamin, and Rebecca Robbins. "Where a vast global vaccination program went wrong." New York Times 2.21 (2021): A1.”. Para ler a meteria completa, você pode acessar este link https://www.nytimes.com/2021/08/02/world/europe/covax-covid-vaccine-problems-africa.html